Some Results of Generalized Extropy Measure and Its application - Kumar, Vikas; Sharma, Salook; Goel, Ritu (Statistics, Optimization & Information Computing, 2025)
Taking into account the importance of extropy (see Lad et al. 2015), and its various generalizations, in the present communication we consider and study the generalized extropy of order alpha and type beta based on Varma's (Varma, 1966) information measure for both discrete and continuous random variables. The dynamic versions (residual and past, both) of the proposed generalized extropy measure have also been presented. At the end, the interval generalized extropy measure and an application of the proposed generalized extropy measure are also presented.